PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF NEARPOD UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS V SD NEGERI 060800 MEDAN AREA - Nababan, Tabita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The science learning outcomes of fifth-grade students at SDN 060800 Medan Area District were still relatively low; therefore, interactive learning media were needed to create a more active, engaging, and meaningful learning process. This study aimed to determine the effect of using Nearpod interactive learning media on the science learning outcomes of fifth-grade students at SDN 060800 Medan Area District. This research employed a quantitative approach using a quasi -experimental method with a Nonequivalent Control Group Design. The sample consisted of 45 students, including 24 students in the experimental class and 21 students in the control class. Data were collected using a learning achievement test and analyzed through descriptive statistics, normality test, homogeneity test, and Independent Samples t-test. The findings revealed that the average science learning outcomes of students in the experimental class were higher than those in the control class. The hypothesis test showed a significance value (Sig. 2-tailed) of 0.000 (< 0.05), with the average posttest score of the experimental class being 82.29, while the control class achieved 73.81. These findings indicate that the use of Nearpod interactive learning media had a significant effect on students' science learning outcomes. This study concludes that Nearpod can be used as an effective alternative learning media to improve science learning outcomes in elementary schools.